«
  
»
Considere o sistema de equacoes \( \dfrac{x-2}{3}+\dfrac{y}{2}=\dfrac{1}{2} \\ x-\dfrac{y-1}{2}=2 \)


RESOLVENDO

\( \dfrac{x-2}{3}+\dfrac{y}{2}=\dfrac{1}{2} \)
\( \dfrac{2(x-2)+3y}{6}=\dfrac{3}{6} \)
\( 2x-4+3y=3 \)
\( \boxed{2x+3y=7} \)
\( x-\dfrac{y-1}{2}=2 \)
\( 2x-y+1=4 \)
\( \boxed{2x-y=3} \)
\( \begin{cases} 2x+3y=7 \\ 2x-y=3\end{cases}~\Rightarrow~\begin{cases}\ 2x+3y=7 \\ -2x+y=-3\end{cases} \)
Somando membro a membro:
\( 4y=4 \)
\( \boxed{y=1} \)
\( 2x-y=3 \)
\( 2x-1=3 \)
\( 2x=4 \)
\( \boxed{x=2} \)
\( \dfrac{y}{x}=\dfrac{1}{2}=0,5 \)
Letra A

A) Multiplique todos os termos por 6:
\( \frac{x-2}{3}+\frac{y}{2}=\frac{1}{2}\\ \\ 2x-4+3y=3\\ \\ \boxed{2x+3y=7} \)
b) Multiplique todos os termos por 2:
\( x-\frac{y-1}{2}=2\\ \\ 2x-y+1=4\\ \\ \boxed{y=2x-3} \)
Substituindo:
\( 2x+3(2x-3)=7\\ \\ 2x+6x-9=7\\ \\ 8x=16\\ \\ \boxed{x=2}\\ \\ Logo \ se: y=2x-3\rightarrow y=2.2-3=1\\ \\ \boxed{y=1} \)
Finalmente,
\( \boxed{\frac{y}{x}=\frac{1}{2}} \)



TAREFAS SIMILARES: